Phenotypic development and eye development in the embryonic and early regenerative phases of the amphibian plum Neurergus crocatus Cope - Ismaeel Hassen; Jehan Younes (College of Education for Pure Sciences, 2006)
The present study dealt with the embryological eye development, growth of its tunics and optics as well as the external morphology of the developmental embryonic stages of the urodclc amphibian Neurergiis crocatus crocalus Cope. The gradual differentiation of eye layers progressed at late embryonic stages which extend between .35 -'39.At these stages the solera and choroids differentiate from mesenchymal cells that surround optic cup. On the other hand the differentiation of neural retina layers occurred. The first layer appeared was ganglion cells at the centrovenlra.l retina toward dorsoventral' retina of 36 stage. The lens fibers was also differentiate at this stage.At stage39distinct development of eye tunics and optics have been occurred, especially the neuralretina layers with increased thickness of the wjiole retina.. All retinal layers were conspicuous except the photoreceptor layer in which only the nuclei were distinct. The axons of ganglion cells bundled to form the optic nerve which penetrate the retina at the lower ventral margin.. The pigment epithelial which loaded with melanosomes also completed. The lens and cornea were became more distinct. .At 40 - 47 larval stages the integration and development of eye parts have been appeared, in that the photoreceptor (cones and rods) were more conspicuous, although the outer segments of these cells were unclear, the apical processes of pigment epithelium extended toward the photoreceptor, the optic nerve path deviated toward the central region of the eye ball and penetration of that region occurred at stage 47, in this stage the formation of ciliary body base, cornea, sclera and choraids were more conspicuous. Histolbgical structure of the adult eye of Neurergus cfocatus , crocatusresemble those of other urodele amphibians generally, in that the retina of duplex type. which consist of rods and cones. The cones nuclei location were vitred while the rods nuclei were sclered.The photoreceptor layer consist of single cone. Single and double rods which have uncleared outer segments in contrast toother amphibians. At last the photoreceptor layer in the present study was not advanced as those in other amphibians.